RELIGIOUS MODERATION IN THE CONTEXT OF ISLAMIC EDUCATION: A MULTIDISCIPLINARY PERSPECTIVE AND ITS APPLICATION IN ISLAMIC EDUCATIONAL INSTITUTIONS IN INDONESIA - Rahmadi Rahmadi; Hamdan Hamdan (Khazanah: Jurnal Studi Islam dan Humaniora, 2023)
This research explores the multifaceted concept of religious moderation within the context of Islamic education in Indonesia. The study investigates four primary aspects: the foundational idea of religious moderation, its diverse perspectives and approaches, the implications of religious moderation in education, and its practical implementation in Islamic educational institutions. Various perspectives on religious moderation education, including theological-normative, sociological, anthropological, and cross-cultural communication perspectives, are examined in detail. Normatively, religious moderation education is guided by the concept of "wasathiyyah" (middle path) along with its defining characteristics. In the sociological aspect, the cultivation of religious moderation is achieved through socialization, fostering individuals to become responsible members of society and citizens who exhibit religious moderation in their social interactions. In the anthropological aspect, religious moderation education is realized through processes of acculturation, encompassing enculturation, socialization, and internalization. Furthermore, the communication aspect highlights the significance of cross-cultural communication as a means to promote religious moderation by facilitating middle-ground communication between diverse cultural backgrounds. The study also underscores the presence of religious moderation content within the scientific traditions of Islamic boarding schools and colleges, emphasizing the importance of preserving and enhancing this aspect. However, it is noted that there is room for improvement in the realm of madrasas, as they still need to strengthen their focus on religious moderation. This can be achieved through deliberate efforts in socialization and fostering a civilizing environment within the madrasah setting. Additionally, incorporating character moderation into the curriculum structure, hidden curriculum, and extracurricular activities is considered vital in nurturing religious moderation among students in madrasas. In conclusion, this research offers valuable insights into the comprehensive understanding and implementation of religious moderation in Islamic education within the Indonesian context. The findings presented here are significant for educators, policymakers, and practitioners seeking to promote a balanced and moderate approach to religious education in the country.